2019
DOI: 10.1111/joop.12257
|View full text |Cite
|
Sign up to set email alerts
|

Do the effects of interpersonal emotion regulation depend on people's underlying motives?

Abstract: Attempts to improve others' feelings have positive consequences, while attempts to worsen others' feelings have negative consequences. But do such effects depend on the motives underlying these attempts? In an experimental study, we tested whether leaders' apparent motives influence the effects of their interpersonal emotion regulation on followers. We found that the positive effects of using affect‐improving (vs. affect‐worsening) strategies on relational outcomes and discretional performance outcomes were la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…For decades, emotion researchers have studied the process of emotion regulation from an internal, or within-person standpoint (e.g., Gross, 1998;Gross & John, 2003), and that within-person focus carried over to research on workplace emotion regulation (Diefendorff et al, 2005(Diefendorff et al, , 2008Grandey, 2000). More recently, researchers have begun to expand our knowledge of emotion regulation by examining it as an external, or interpersonal phenomenon (Little et al, 2012(Little et al, , 2015(Little et al, , 2016Niven, 2016;Niven et al, 2019;Nozaki & Mikolajczak, 2020;Reeck et al, 2016;Thiel et al, 2015;Troth et al, 2018;Zaki & Williams, 2013). The intentional act of influencing another person's emotional state has been given many names, including interpersonal emotion regulation (Niven, 2016;Zaki & Williams, 2013), extrinsic emotion regulation (Nozaki & Mikolajczak, 2020), social regulation of emotion (Reeck et al, 2016), and interpersonal emotion management (Toegel et al, 2012).…”
Section: Interpersonal Emotion Managementmentioning
confidence: 99%
“…For decades, emotion researchers have studied the process of emotion regulation from an internal, or within-person standpoint (e.g., Gross, 1998;Gross & John, 2003), and that within-person focus carried over to research on workplace emotion regulation (Diefendorff et al, 2005(Diefendorff et al, , 2008Grandey, 2000). More recently, researchers have begun to expand our knowledge of emotion regulation by examining it as an external, or interpersonal phenomenon (Little et al, 2012(Little et al, , 2015(Little et al, , 2016Niven, 2016;Niven et al, 2019;Nozaki & Mikolajczak, 2020;Reeck et al, 2016;Thiel et al, 2015;Troth et al, 2018;Zaki & Williams, 2013). The intentional act of influencing another person's emotional state has been given many names, including interpersonal emotion regulation (Niven, 2016;Zaki & Williams, 2013), extrinsic emotion regulation (Nozaki & Mikolajczak, 2020), social regulation of emotion (Reeck et al, 2016), and interpersonal emotion management (Toegel et al, 2012).…”
Section: Interpersonal Emotion Managementmentioning
confidence: 99%
“…Finally, other attributional dimensions need to be considered. Recent studies on surface acting [ 15 ] and interpersonal regulation of emotions [ 14 ] have shown that the attributions that people make about motives to influence the feelings of others positively or negatively are related to the quality of the leader–member relationship. Employees’ attributions regarding the stability of client behavior (e.g., the employee’s perception of the client’s current behavior reflects the way he usually behaves) or the presence of egoistic motives (e.g., the employee believes the passenger had no intention to take the flight and is pretending he missed the flight to claim compensation) can also contribute to increasing the employee’s perception of distributive injustice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the negative impact of surface acting partially depends on employees´ attributions for the emotional demands. Niven et al (2019) [ 14 ] showed that the attributions employees make about the motives people hold to influence the feelings of others either positively or negatively are related to the quality of their relationship with leaders. Yagil (2020) [ 15 ] found that employees’ attributions related to the stability of client behavior (e.g., the employee’s perception that the client’s current behavior reflects the way he usually behaves) or the presence of egoistic motives can also contribute to increasing the employee’s perception of distributive injustice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Niven (2016) explains, “regulatory processes like interpersonal emotion regulation can only be truly understood with reference to the motives that underlie them” (p. 306). A particularly fundamental aspect of motivation for interpersonal emotion regulation concerns whether it is driven by egocentric or prosocial goals (Niven, 2016; Niven, Troth, et al, 2019). In the first case, individuals regulate the emotions of others to achieve their own goals, while in the latter, individuals are motivated to help others to reach their goals.…”
Section: Introductionmentioning
confidence: 99%